On the importance of non-equilibrium effect in microchannel two-phase boiling flow. (March 2020) - He, Hui; Pan, Liang-ming; Wei, Lie; Zhang, Mu-hao; Zhang, Ding-fei
Highlights: A heuristic method to predict vapor quality for both stable flow and reversed flow in microchannel is proposed. Experiments in microchannel are performed to investigate non-equilibrium effects on vapor quality. Thermodynamic equilibrium quality can provide accurate measure of vapor content for stable flow. Maximum non-equilibrium effect accounts for 51.8% of total vapor quality variation within the extent of experimental conditions. Abstract: The current paper develops a heuristic method taking into account the non-equilibrium effects to predict the vapor quality for both stable flow and reversed flow in microchannel. Experiments of two-phase boiling flow in a microchannel heat sink which contains 14 parallel 0.15 × 0.25 mm rectangular microchannels with hydraulic diameter of Dh  = 187.5 µm by using deionized water as working fluid are also performed to investigate the non-equilibrium effects on the vapor quality. Thermodynamic equilibrium quality can provide an accurate measure of vapor content for stable flow in multi-parallel microchannels due to a negligible subcooling boiling region. The majority of data can be satisfactorily predicted by thermodynamic equilibrium quality with the maximum relative error of -10% in the vicinity of the channel outlet with the exception of the largest heat flux/mass flux ratio case since dryout occurs with the presence of superheated vapor at the channel outlet. A notable difference resides in thermodynamic equilibrium quality and the actual vapor quality predicted by the current method except near the downstream of channel due to the saturated boiling flow for reversed flow, and this trend becomes increasingly evident at upstream region of the channel by reason of the strong mixing of the backflow vapor bubble with the incoming subcooled liquid. In addition, the contribution of non-equilibrium effect decreases along with the channel axial direction and exhibits a decreasing trend as the mass flux increased with its maximum value accounting for approximately 51.8% of total vapor quality variation.